A useful anaesthetic technique for ovarian germ cell tumour along with acute kidney injury in young Asian lady - Dileep Kumar; Muhammad Suleman; Mehreen Malik (Journal of the Pakistan Medical Association, 2021)
We report mixed germ cell tumour, presented with acute kidney injury in an unmarried 22 years old Asian girl. Our case demonstrated an aggressive approach with multidisciplinary teamwork ascertained outstanding clinical outcome. She managed successfully for fertility-sparing surgery and three cycles of Bleomycin, Etoposide and Cisplatin (BEP) therapy. Patient’s pathophysiology returned to normal within weeks and she converted tumour-free. Furthermore, the three years follow up scans and biomarkers were evident for tumour negativity. Continuous...